Effect of carboxymethyl cellulose and palm oil mill effluent (POME) as binding agents on the pelletization of waste wood - Kartik Raj, Kannan; Yuganvarma, Ramasamy; Najaatul Aimi, Sollahunddin; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (AIP Publishing, 2025)
Pelletization is a method of converting biomass waste into biofuel through compacting biomass into uniform, high-density pellets. However, biomass pellet forms from pelletization process have poor pellet quality and high dust formation during handling, transportation and storage. Thus, suitable binding agent is required for providing the necessary cohesion and strength of the pellet. Thus, the objective of this work is to study the effect of different binding agents such as carboxymethyl cellulose (CMC) and palm oil mill effluent (POME) on the quality of pellet in terms of its strength, properties and combustion behaviour. In this study, waste woods (Seraya (Shorea curtisii) and Mengkulang (Heritiera)) were combined with the binding agents (CMC and POME) with different composition ratios (100:0, 75:25 and 50:50) to produce co-pellet. Initially, the raw materials were ground to reduce the sample size in the range of 0.5 mm to 1.0 mm. Afterwards, the samples undergone the pelletization process in which the samples were exposed to a hot press machine with a range of compositions, binding agents and water. The samples were then subjected to a variety of tests, including a combustion test, a mechanical strength test to evaluate the durability of pellets, a moisture content analysis, a Thermogravimetric Analysis (TGA), and ash content. It was found that wood samples bound with CMC exhibit superior mechanical properties compared to those made with palm oil mill effluent (POME). Additionally, a 50:50 composition ratio of wood and binding agent offers greater compression endurance and improved combustion efficiency, with CMC-bound pellets are burning faster and producing less ash than POME-bound ones. Consequently, incorporating CMC as a binder in wood pellets at a 50:50 ratio is recommended to enhance mechanical strength, combustion efficiency, and reduce ash content for applications like combustion units, thermal power plants, and electricity production as an alternative to coal.